ANALISIS KUALITAS KINERJA PERUSAHAAN DENGAN METODE MANAGEMENT BY OBJECTIVES (MBO) PADA CV. WIDYA - Muhammad Zidane; Ade Momon S (Industry Xplore, 2023)
The quality of employee performance can be generated by habits within the company. Various concept efforts are made to improve the quality of performance. Therefore, human resources need to be developed consistently to achieve the actual quality of performance. The purpose of this research is performance quality research at CV Widya based on employee performance appraisals from raw materials, production, packaging and distribution using the Management By Objectives (MBO) method which consists of Planning, Monitoring and Review. The results of the study are explained as a result of the analysis in the field during the research obtained suggestions including CV. Widya must maintain the quality of the company's performance, CV. Widya is expected to conduct regular evaluations, in the production and packaging processes. Based on the research results described earlier, as a result of the analysis of observations and interviews, it can be concluded that the quality of employee performance at CV Widya can be concluded to be effective based on employee performance appraisals using the Management By Objectives (MBO) method which consists of Planning, Monitoring and Review. Although there are some that must be corrected, it is quite mild to be corrected.Keywords: Management by objectives; Performance quality; Supply chain management